The Structural Relationship of Academic Engagement Based on Mindfulness with the Mediating Role of Academic Burnout and Academic Self-handicapping in Students - Mostafavi, Elham; Vatankhah, Hamidreza; Khalatbari, Javad (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The purpose of this research was to predict academic engagement based on mindfulness with the mediating role of academic burnout and academic self-impairment among Azad University students. Methods and Materials: The research was a descriptive-correlational study. The statistical population includes all students of Azad University of Tehran who were studying in the academic year 2020-21, the target sample was selected using random sampling method in the number of 350 people. In order to analyze the data, it was analyzed using the structural equation method of factor analysis with the help of AMOS software. Data collection tools were: Reeve Academic Involvement Questionnaire (2013), Freiburg Mindfulness Questionnaire (FMI-SF), Academic Boredom Questionnaire by Pekrun et al. (2020), and Jones Academic Self-Disability Questionnaire (2020); and the results of factor analysis and Cronbach’s alpha also confirmed their validity and reliability. Findings: The results showed mindfulness (B=0.38, P<0.001) directly and positively and academic self-disability (B=0.29, P<0.001) and academic boredom (B=0.24, P<0.001) predict academic engagement. In addition, the proposed research model had a good fit. Conclusion: It can be concluded that mindfulness has a significant effect on the academic engagement of students due to the mediating role of academic boredom and academic self-handicapping.